Reducing the Energy Consumption of a Central Air Conditioning Facility Based on Condensation Water Generated by This Facility - ديبة جابر; حيدر عقبة (Latakia University Journal -Engineering Sciences Series, 2021)
The electrical energy used to cover the air-conditioning capacity is a significant and large part of the total energy consumption, especially with the increasing use of VCR Vapor compression refrigeration systems. Therefore, it was necessary to search for technologies that allow reducing the energy consumption of these systems, or replace them with more efficient and less consuming systems. The presented research, which dealt with the central air conditioning system at Tishreen University Hospital in Lattakia, shows the large amount of water produced by air conditioning systems from air handling units during the summer season, in humid climates such as Lattakia city, which is often wasted without benefiting from it. The study shows the importance of using this water in the pre-cooling process, which allows reducing energy consumption, especially in establishments where health conditions do not allow the use of return air in the process of reducing capacity through the mixing box within the AHU units, as the results show the possibility of achieving a reduction in the required capacity of the treatment unit by a percentage 12.23% and reducing the facility’s operating capacity by about 1.3% through utilizing this water.